PEMBENTUKAN IDENTITAS ETNIS DAN ARSITEKTUR BANGUNAN DI KALIMANTAN TENGAH - Desembeling, Desembeling (Fakultas Dharma Duta, 2025)
This study examines the emergence of Dayak traditional architecture in building designs across Central Kalimantan Province. Rather than being a spontaneous development, the prominence of ethnic-inspired architecture reflects a deliberate process of construction and standardization. A key milestone was the seminar organized by Ikatan Arsitek Indonesia (IAI) and Ikatan Konsultan Indonesia (INKINDO) of Central Kalimantan on September 14, 1996, which formalized the notion of Dayak traditional architecture. Drawing primarily on reports from Pelita Pembangunan newspaper, this paper analyzes the narratives formulated before, during, and after the seminar. The findings suggest that the dissemination of Dayak architectural forms can be understood as a systematic process of narrative building, corresponding to what Hobsbawm terms the “Invention of Tradition.”